A Contribution to Systems-of-Systems Concept Standardization - Ed-daoui, Ilyas; El Hami, Abdelkhalak; Itmi, Mhamed; Hmina, Nabil; Mazri, Tomader (International Journal of Engineering and Technology, 2018)
This paper aims to continue the work towards the standardization of the concept of systems-of-systems (SoS). A notion that has been around for quite a while, but still difficult to unanimously agree on one definition for it. Correspondingly, we collected some SoS definitions from literature in order to point out the similarities between them. We present a set of SoS characteristics that differentiate them from classic and complex systems. A classification of SoS is also detailed. Eventually, an application is presented in order to emphasize the importance of the classification.Â Â Â
Keywords: Systems-of-systems (SoS); SoS classification; SoS characteristics; SoS classification.